Mediators of the effects of an HIV prevention advocacy training intervention on prevention advocacy among persons living with HIV in Uganda - Glenn J. Wagner; Laura M. Bogart; Joseph K. B. Matovu; Violet Gwokyalya; Harold D. Green; Susan Ninsiima; David J. Klein; Stephen Okoboi (Journal of Behavioral Medicine, 2026)
Abstract Pathways through which advocacy training enhances engagement in advocacy among persons living with HIV (PLWH) are not well understood. In a secondary analysis from a randomized controlled trial of a peer advocacy training intervention for PLWH, we examined mediators of intervention effects on HIV prevention advocacy (i.e., encouraging others to engage in HIV protective behaviors) across members of their social network. A sample of 210 PLWH (105 in each of the intervention and control arms) provided information about their advocacy to their social network members at baseline, and 6-, 12-, and 18-month follow-up. Repeated measures linear regressions showed that PLWH in the intervention group targeted more social network members with advocacy for HIV testing, condom use, pre-exposure prophylaxis (PrEP) use, HIV care, and ART use over the follow-up period compared to those in the control group. In path analysis that examined each mediator in a separate model, reduced internalized HIV stigma and increased HIV knowledge as measured at month 6, each fully mediated the intervention effect on HIV care advocacy; reduced stigma partially mediated the effects on advocacy targeting each of the other four HIV protective behaviors, while increased knowledge partially mediated effects on HIV testing, condom and PrEP use advocacy. Results were unchanged when examining the joint mediation of stigma and knowledge. HIV disclosure and advocacy self-efficacy had no mediating effect. These findings highlight the importance of helping PLWH to cope with HIV stigma and gain knowledge about basic facts and common misconceptions related to HIV, to propel their engagement in advocacy for multiple HIV protective behaviors within their social networks. The trial was registered 2021-10-18 (NCT05098015).